Proteomic Profiling of Neuroblastoma Cells Adhesion on Hyaluronic Acid-Based Surface for Neural Tissue Engineering. (7th December 2016) - Yang, Ming-Hui; Chen, Ko-Chin; Chiang, Pei-Wen; Chung, Tze-Wen; Chen, Wan-Jou; Chu, Pei-Yu; Chen, Sharon Chia-Ju; Lu, Yi-Shan; Yuan, Cheng-Hui; Wang, Ming-Chen; Lin, Chia-Yang; Huang, Ying-Fong; et al.
Abstract : The microenvironment of neuron cells plays a crucial role in regulating neural development and regeneration. Hyaluronic acid (HA) biomaterial has been applied in a wide range of medical and biological fields and plays important roles in neural regeneration. PC12 cells have been reported to be capable of endogenous NGF synthesis and secretion. The purpose of this research was to assess the effect of HA biomaterial combining with PC12 cells conditioned media (PC12 CM) in neural regeneration. Using SH-SY5Y cells as an experimental model, we found that supporting with PC12 CM enhanced HA function in SH-SY5Y cell proliferation and adhesion. Through RP-nano-UPLC-ESI-MS/MS analyses, we identified increased expression of HSP60 and RanBP2 in SH-SY5Y cells grown on HA-modified surface with cotreatment of PC12 CM. Moreover, we also identified factors that were secreted from PC12 cells and may promote SH-SY5Y cell proliferation and adhesion. Here, we proposed a biomaterial surface enriched with neurotrophic factors for nerve regeneration application.